Harnessing dual applications of a novel ascomycetes yeast, Starmerella cerana sp. nov., as a biocatalyst for stereoselective ketone reduction and biosurfactant production - Kumar, Sachin; Verma, Nitish Kumar; Basotra, Sandal Deep; Sharma, Divya; Prasad, G. S.; Bhattacharyya, Mani Shankar (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: New bioresources for catalytic application and fine chemical synthesis are the need of the hour. In an effort to find out new biocatalyst for oxidation-reduction reaction, leading to the synthesis of chiral intermediates, novel yeast were isolated from unique niche and employed for the synthesis of value added compounds. Methods: To determine the genetic relatedness of the isolated strain, HSB-15T, sequence analysis of the internal transcribed spacer (ITS) and D1/D2 domains of the 26S rRNA gene sequence was carried out. The distinctive features of the strain HSB-15T were also identified by phenotypic characterization. The isolated strain HSB-15T was employed for the reduction of selected naphthyl ketones to their corresponding alcohols and a biosurfactant was isolated from its culture broth. Results: The analysis of the ITS and D1/D2 domains of the 26S rRNA gene revealed that strain HSB-15T is closely related to the type strain of Starmerella vitae (CBS 15147T) with 96.3% and 97.7% sequence similarity, respectively. However, concatenated sequences of the ITS gene and D1/D2 domain showed 94.6% sequence similarity. Phenotypic characterization indicated significant differences between strain HSB-15T and its closely related species and consequently, it was identified as a novel species, leading to the proposal of the name Starmerella cerana sp. nov. The strain was able to reduce selected naphthyl ketones to their corresponding alcohols with remarkable efficiency, within a 12-hours. The strain HSB-15T also produced a surfactant in its culture broth, identified as sophorolipid upon analysis. Discussion: The study explored the potential of the novel strain, HSB-15T, as a whole-cell biocatalyst for the reduction of naphthyl ketones to their corresponding alcohols and also reports its capability to produce sophorolipid, a biosurfactant, in its culture broth. This dual functionality of HSB-15T both as biocatalyst and biosurfactant producer enhances its applicability in biotechnology and environmental science.